2014
DOI: 10.1089/dia.2013.0184
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Partial Pressure of Oxygen in Blood Samples on the Performance of Systems for Self-Monitoring of Blood Glucose

Abstract: Background: The partial pressure of oxygen (pO 2 ) in blood samples can affect glucose measurements with oxygen-sensitive systems. In this study, we assessed the influence of different pO 2 levels on blood glucose (BG) measurements with five glucose oxidase (GOD) systems and one glucose dehydrogenase (GDH) system. All selected GOD systems were indicated by the manufacturers to be sensitive to increased oxygen content of the blood sample. Materials and Methods: Venous blood samples of 16 subjects (eight women, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
(40 reference statements)
1
15
0
Order By: Relevance
“…Particularly at pO 2 ≤45 mmHg, we found considerably overestimated measurements. 2 Decreased pO 2 values can occur in patients with respiratory diseases, such as chronic obstructive pulmonary disease, 3 which is described as being associated with type 2 diabetes. 4 At high altitudes or also during long-distance flights, up to ~40% decreased pO 2 is reported for arterial blood samples; 5 a similar behavior can also be expected for capillary blood samples from the fingertip.…”
Section: J Diabetes Sci Technol Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly at pO 2 ≤45 mmHg, we found considerably overestimated measurements. 2 Decreased pO 2 values can occur in patients with respiratory diseases, such as chronic obstructive pulmonary disease, 3 which is described as being associated with type 2 diabetes. 4 At high altitudes or also during long-distance flights, up to ~40% decreased pO 2 is reported for arterial blood samples; 5 a similar behavior can also be expected for capillary blood samples from the fingertip.…”
Section: J Diabetes Sci Technol Letter To the Editormentioning
confidence: 99%
“…Beside other interfering factors, the blood samples' partial pressure of oxygen (pO 2 ) can affect BG measurements, particularly in systems based on glucose oxidase (GOx) enzyme reactions on test strips. 1,2 Indeed, many of the available home-use systems for self-monitoring of blood glucose (SMBG) utilize the GOx enzyme reaction, which is prone to oxygen interference; however, in the literature, poor information is available concerning physiological pO 2 values and possible variations in capillary blood from the fingertip in people with diabetes.…”
mentioning
confidence: 99%
“…Although interstitial enzyme-based continuous glucose monitoring is Hypoglycaemia Increased energy expenditure without concomitant increases in carbohydrate intake and/or reductions in insulin, insulin secretagogues and/or oral antihyperglycaemic agents Decreased appetite without lowering insulin or insulin secretagogue medication Blunted epinephrine responses due to antecedent hypoglycaemia and/or exercise Vomiting, diarrhoea and illness without reductions in insulin or insulin secretagogue medications Over-treatment of hyperglycaemia with insulin or insulin secretagogue medications in a setting of increased physical activity Unintentional insulin delivery from insulin pump due to reduced barometric pressure and gas bubble formation in pump reservoir, which increases reservoir pressure [57] High-altitude-induced impairment in postprandial carbohydrate absorption rate [3,26] Hyperglycaemia Increased physiological stress of highaltitude trekking (raised sympathetic activity and counter-regulatory hormones, thereby increasing glucose production and limiting glucose disposal) Psychological stress: fear of climbing, remote locations, no medical companion Stress response to acute illness, injuries and/ or trauma or sunburn AMS, promoting higher sympathetic activity and increased cortisol levels Exposure of insulin to extreme temperatures ( < 2°C or > 30°C), thereby reducing potency Dehydration Excessive fear of hypoglycaemia promoting too aggressive reductions in insulin or other insulin secretagogue medications, or excessive carbohydrate consumption without appropriate treatment Blood glucose meters underestimating true glucose levels, making the individual more inclined to treat for hypoglycaemia when glucose levels are normal or elevated Increased glycolytic flux during exercise at high altitude [58] functional and useful for tracking glycaemia at high altitude [21], the accuracy of blood glucose meters can become compromised at altitude for a variety of reasons [4][5][6], which may also affect calibration of continuous glucose-monitoring equipment. Although, in theory, oxygen saturation could impact meter accuracy in those using glucose oxidase (GOX) enzymes, it does not appear to impact meter accuracy in those using the glucose dehydrogenase (GDH) reaction pathway, at least to altitudes of~3000 m [31]. Alterations in haematocrit levels with altitude may also reduce meter accuracy, but about half of new meters tested have been shown to reliably correct for the potential influence of haematocrit level on the meter result [30].…”
Section: Glucose Meter Performancementioning
confidence: 99%
“…Alterations in haematocrit levels with altitude may also reduce meter accuracy, but about half of new meters tested have been shown to reliably correct for the potential influence of haematocrit level on the meter result [30]. Although, in theory, oxygen saturation could impact meter accuracy in those using glucose oxidase (GOX) enzymes, it does not appear to impact meter accuracy in those using the glucose dehydrogenase (GDH) reaction pathway, at least to altitudes of~3000 m [31]. However, a recent investigation of two meters using GDH and two using GOX at simulated altitude (~8000 ft) did not show any difference in accuracy between meter types, although all four meters studied tended to overestimate glucose levels slightly when values were in the hyperglycaemic range [32].…”
Section: Glucose Meter Performancementioning
confidence: 99%
“…Schmid et al 8 evaluated five glucose oxidase-based systems and demonstrated positive biases between 11.8% and 44.5% caused by low pO 2 (<45 mm Hg) and negative biases of −14.6% to −20.2% caused by high pO 2 (>150 mm Hg) relative to samples at capillary pO 2 (70 mm Hg). They concluded that “the pO 2 range in which the systems operate well should be investigated further and should be provided in the product information”.…”
mentioning
confidence: 99%